2021
DOI: 10.1016/j.epsl.2021.117059
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of equilibrium iron isotope fractionation in Fe1−S alloys at Earth's core formation conditions

Abstract: Iron is one of the most abundant non-volatile elements in the solar system. As a major component of planetary metallic alloys, its immiscibility with silicates plays a major role in planetary formation and differentiation. Information about these processes can be gained by studying the equilibrium Fe isotope fractionation between metal alloys and molten silicates at conditions of core formation. In particular, recent attention has been paid to 56 Fe/ 54 Fe equilibrium isotope fractionation at conditions releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…However, outside this exception, the similar Fe 𝛽-factors obtained by the "VAF" and the "snapshot" methods allow to conclude that both methods are relevant to determine the isotopic properties of a melt. This conclusion was previously reached by Pinilla et al (2021) in the case of Fe-S alloys at high pressure and temperature conditions. This also means that potential anharmonic effects, that are at least partially taken in account with the "VAF" method, are negligible considering the uncertainties obtained and that extrapolation of Fe 𝛽-factors at high temperature from force constants obtained at low temperature is relevant (e.g.…”
Section: Reduced Partition Function Ratios Of Iron and Siliconsupporting
confidence: 69%
See 1 more Smart Citation
“…However, outside this exception, the similar Fe 𝛽-factors obtained by the "VAF" and the "snapshot" methods allow to conclude that both methods are relevant to determine the isotopic properties of a melt. This conclusion was previously reached by Pinilla et al (2021) in the case of Fe-S alloys at high pressure and temperature conditions. This also means that potential anharmonic effects, that are at least partially taken in account with the "VAF" method, are negligible considering the uncertainties obtained and that extrapolation of Fe 𝛽-factors at high temperature from force constants obtained at low temperature is relevant (e.g.…”
Section: Reduced Partition Function Ratios Of Iron and Siliconsupporting
confidence: 69%
“…Such corrections in complex silicate melts would be difficult to achieve since it would require precise knowledge of the molar volume contribution of each species in the melt. Furthermore, Pinilla et al (2021) showed that these fluidicity effects were negligible in the calculation of equilibrium fractionation factor of iron in liquid Fex-1Sx alloys. Therefore, such effects were neglected here.…”
Section: -The "Vaf" Methodsmentioning
confidence: 99%
“…where K is the atomic kinetic energy, can be obtained by determining the partial vibrational density of states (VDOS) based on the velocity autocorrelation function 72,73 . This method incorporates anharmonic effects on the structures, but its effectiveness relies on the length of the trajectory used to obtain meaningful results given that the noise in the velocity auto-correlation function increases with the length of the time interval and could lead to nonconverged spectra 73 . Moreover, the VDOS displays a non-zero value at zero frequency due to diffusion effects, which should be removed before calculating β, posing a challenge 72 .…”
Section: Equilibrium Isotope Fractionationmentioning
confidence: 99%
“…Moreover, the VDOS displays a non-zero value at zero frequency due to diffusion effects, which should be removed before calculating β, posing a challenge 72 . Furthermore, deriving β in this way may introduce systematic errors when compared with β values of minerals obtained from full vibrational frequencies calculated under static conditions 73 .…”
Section: Equilibrium Isotope Fractionationmentioning
confidence: 99%
“…Calculation of equilibrium constants of isotope exchange reactions via RPFR was first proposed by Bigeleisen and Mayer and has been widely used to study isotope exchange reactions. The main advantage of the Bigeleisen and Mayer approach is that it allows calculating the isotope exchange equilibrium constants solely via normal mode vibrational frequencies. Considering that those vibrational frequencies can be obtained also experimentally and therefore without requiring calculations of principal moments of inertia for the molecules, the Bigeleisen and Mayer approach provides a practical way to evaluate the required equilibrium constants.…”
Section: Theorymentioning
confidence: 99%